Design and commissioning of experiments for supersonic ORC nozzles in linear cascade configuration. (April 2023) - Manfredi, Marco; Persico, Giacomo; Spinelli, Andrea; Gaetani, Paolo; Dossena, Vincenzo
Abstract: In organic Rankine cycle (ORC) power systems, the turbo-expander involves the major technical challenges as the demand for compactness and flexibility of operation couples with severe compressibility and non-ideal gas effects. For these reasons the design of ORC turbines heavily relies on advanced aerodynamic models, whose validation is crucial but is still limited due to a lack of experimental data. To fill this gap, an experimental campaign on supersonic ORC nozzle cascades has been launched at Politecnico di Milano. This paper describes the conception and set-up of a novel class of experiments on linear cascades representative of stator nozzles of axial/radial ORC turbines, and aims at serving as a reference for future experimental investigations on ORC cascades. The paper also discusses the technical challenges of performing measurements on supersonic flows for a vapor at thermodynamic conditions close to saturation. Moreover, the paper reviews all steps required to design the campaign, discussing the blade design and the numerical simulations performed to assess the flow configuration in the linear cascade, with emphasis on the periodicity of the flow. The main objective of the experiments is to investigate the flow phenomena occurring in the blade trailing edge region and to retrieve the total pressure losses through the cascade with a relatively high spatial resolution, aiming at providing a benchmark for numerical simulations. To this end, the set of measurement techniques includes supersonic total pressure probes and wall pressure taps, as well as thermo-couples and schlieren visualizations. The main result of this preliminary work is the implementation of a relatively simple methodology to carry out experiments in blade cascade operated with organic vapors and aimed at evaluating cascade losses, without resorting to specifically calibrated instrumentation. Graphical abstract: Highlights: Innovative tests on linear ORC turbine rows operated with siloxane MM were designed. A reliable measuring system to assess losses in supersonic cascades was implemented. A traversing system with spatial resolution suited for CFD comparison was conceived. A linear cascade representative of supersonic ORC turbine nozzles was designed. Early experiments were performed in non-ideal thermodynamic conditions.